Effect of LPS treatment on the viability and chemokine synthesis by epithelial cells and gingival fibroblasts. Issue 8 (August 2015) - Basso, F.G.; Soares, D.G.; Pansani, T.N.; Turrioni, A.P.S.; Scheffel, D.L.; de Souza Costa, C.A.; Hebling, J.
Highlights: The effect of prolonged contact with lipopolysaccharide (LPS) on oral mucosal cells was evaluated. Prolonged LPS contact was used to simulate a prolonged inflammatory stimulus. Prolonged LPS contact with oral mucosal cells negatively influenced cell functions. Prolonged LPS contact can decrease the viability of oral mucosal cells. Prolonged LPS contact increased the chemokine expression of oral mucosal cells. Abstract: Objective: Several local factors can affect the wound-healing process, delaying its progression and postponing tissue homeostasis. It is known that local inflammation is related to wound healing; however, the maintenance of the inflammatory reaction can impair the proliferation and migration of oral mucosal cells. The aim of this study was to evaluate the viability and chemokine expression of epithelial cells and gingival fibroblasts exposed to long-term lipopolysaccharide (LPS) treatment. Design: Epithelial cells (HaCaT, Cell Lines Service, 300493) and human gingival fibroblasts (HGFs) were seeded (1 × 10 5 cells/well) in 24-well plates and incubated for 24 h. To simulate the responses of cells to a local chronic oral mucosal inflammation, we added LPS of Escherichia coli (10 μg/ml) to Dulbecco's modified Eagle's medium (DMEM), kept in contact with fibroblasts and epithelial cells for 24, 48, and 72 h. Then the cells were assessed for viability (alamarBlue assay), number (trypan blue assay), and expression of CCL2 and CCL5 inflammatory chemokines (enzyme-linked immunosorbent assay (ELISA)). Data were statistically analyzed by nonparametric Kruskal–Wallis and Mann–Whitney tests at a significance level of 5%. Results: Cell treatment with LPS caused significant decrease in viability for both cell lines. No time-dependent effect was observed for epithelial cells. However, reduction in fibroblast viability was greater at 48 and 72 h. CCL2 and CCL5 synthesis was significantly increased for both LPS-treated cells, and this expression decreased with time. Conclusion: The maintenance of an inflammatory cell stimulus by LPS decreases the number and viability of cultured oral mucosal cells, which may be related to delayed wound healing.